2009
DOI: 10.1186/1465-9921-10-59
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of salmeterol/fluticasone propionate by GOLD stage of chronic obstructive pulmonary disease: analysis from the randomised, placebo-controlled TORCH study

Abstract: Background: The efficacy of inhaled salmeterol plus fluticasone propionate (SFC) in patients with severe or very severe COPD is well documented. However, there are only limited data about the influence of GOLD severity staging on the effectiveness of SFC, particularly in patients with milder disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
231
1
17

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(266 citation statements)
references
References 14 publications
17
231
1
17
Order By: Relevance
“…Large clinical trials have already documented the benefit of longacting bronchodilators, in terms of lung function, health status, hospitalisation, exacerbation rates, and mortality. [12][13][14][15] In the present study, the overall use of LABA and LAMA were only about 17% and 7%, respectively. This inappropriately low prescription rate of long-acting bronchodilators had also been demonstrated in a previous local study.…”
Section: Discussionmentioning
confidence: 99%
“…Large clinical trials have already documented the benefit of longacting bronchodilators, in terms of lung function, health status, hospitalisation, exacerbation rates, and mortality. [12][13][14][15] In the present study, the overall use of LABA and LAMA were only about 17% and 7%, respectively. This inappropriately low prescription rate of long-acting bronchodilators had also been demonstrated in a previous local study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a post hoc analysis examined the effects of salmeterol/fluticasone combination therapy by disease stage focusing on moderate COPD. 26 In patients with moderate COPD, this analysis showed significant improvement in post-bronchodilator FEV1 and health status, and a reduction in exacerbation rates compared to placebo. Another post hoc analysis focusing on those with moderate disease, showed better health status and longer time to first exacerbation in the group treated with tiotropium compared to placebo.…”
Section: Introductionmentioning
confidence: 81%
“…Hyperinflation impacts upon a patient's inspiratory capacity, increases functional residual capacity and limits exercise capability [1]. Similarly, post hoc analyses of data from the TORCH (Towards a Revolution in COPD Health), UPLIFT (Understanding Potential Long-term Impacts on Function with Tiotropium) and ECLIPSE (Evaluation of COPD Longitudinally to Identify Predictive Surrogate End-points) studies found that pulmonary function decline is faster in the earlier stages of disease [10][11][12][13].…”
Section: Rationale For Early Treatmentmentioning
confidence: 99%
“…There is evidence that lung function, health status and dyspnoea in patients with mildto-moderate COPD can be improved with single-agent pharmacotherapy [21][22][23][24]. Subgroup analyses of clinical trials suggest that pharmacotherapy may also reduce the rate in forced expiratory volume in 1 s (FEV1) decline versus placebo in patients with early stages of the disease [11,12,25]. Therefore, we speculate that intervention with long-acting bronchodilators at an early stage in disease could prove beneficial and may improve patient-reported outcomes.…”
Section: Rationale For Early Treatmentmentioning
confidence: 99%